Hubungan antara Perilaku Overprotective Orang Tua dengan Penyesuaian Diri pada Mahasiswa Rantau Tahun Pertama di Yogyakarta - Beauty Cesya Mutiara; Anwar Anwar; Martaria Rizky Rinaldi (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2021)
This study aims to determine the relationship between overprotective parental behavior with adjustment in first-year overseas students in Yogyakarta. The hypothesis proposed is that there is a negative relationship between overprotective behavior of parents with adjustment to the first-year overseas students in Yogyakarta. The subjects in this study were 60 first-year overseas students in Yogyakarta . The data collection in this study used the overprotective behavior scale and the Adjustment scale. The data analysis technique used is the product moment correlation from Karl Person. Based on the results of data analysis obtained correlation coefficient r = - 0.226, (p 0.050), indicating there is a negative relationship to overprotective parental behavior with the adjustment of overseas students. The overprotective behavior variable contributed 5.1% to the low adjustment and the remaining 94.9% was influenced by other factors.